Amstal expression patterns in the Qur'an and Hadith and their application in Arabic learning - Oman Karya Suhada; Jimatul Arrobi (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2022)
Abstract : This study discusses the pattern of the expression